Islamic Banking Selection Criteria: Case in Türkiye using Analytic Network Process (ANP) - Adam, Muniem (Islamic Social Finance, 2024)
The Islamic banking sector is presently a key marker of the advancement of Islamic economics in Türkiye. Among the various aspects of Islamic banking, understanding individuals' preferences and behaviors toward these institutions is of particular importance. The investigation of factors influencing bank selection has been a prominent focus for researchers in banking and marketing. However, compared to conventional banking, studies addressing this subject remain comparatively rare, especially within the context of Türkiye. This research aims to examine the preferences and behavioral criteria influencing the selection of Islamic banks among foreign students in Türkiye, utilizing the Analytical Network Process (ANP) methodology as its analytical framework. The findings indicate that the primary criteria influencing the selection of Islamic banks in Türkiye are the quality of service, advancements in technology, and religiosity factors, specifically the alignment of banking practices with Sharia principles. Consequently, it is crucial for Islamic bank marketers and stakeholders to prioritize the ongoing improvement of product and service quality to maintain competitiveness with conventional banks. The formulation and execution of robust business and marketing strategies are essential to fostering a sense of comfort and convenience for both existing and prospective customers. The results further demonstrate that Ziraat Katılım is the leading choice among Islamic banks, with Albaraka ranking second.